Mobilization and Immobilization of Zinc Oxide Nanoparticles by Phomopsis sp. Isolated HM1 - Sutjaritvorakul, T.; Imsuwan, P.; Mongkolaussavarat, T.; Chutipaijit, S. (Thai Journal of Nanoscience and Nanotechnology, 2016)
Phomopsis sp. isolated HM 1 was isolated from zinc-containing rocks (Hemimorphite). It was screened for the ability to solubilize and immobilize zinc oxide nanoparticles (ZnONPs). Fungal strain was plated on potato dextrose agar (PDA) medium, which was supplemented with various concentrations of zinc oxide nanoparticles. Phomopsis sp. isolated HM 1 showed the highest efficiency for solubilizing zinc oxide nanoparticles, producing clearing zone diameters more than 40 mm in 0.1, 0.3 and 0.5% (w/v) of ZnONPs amended plates. Mycogenic crystals were observed in the agar medium underneath the fungal colonies of tested strain. The crystals were identified by scanning electron microscope (SEM) and X-ray powder diffraction (XRPD) and were identified as zinc oxalate hydrate (C2O4Zn·2H2O). Therefore, it could be suggested that this fungal strain might has the potential application in agriculture and bioremediation practice of heavy metals contaminated soils.